2011
DOI: 10.1063/1.3560921
|View full text |Cite
|
Sign up to set email alerts
|

Analytical device model for graphene bilayer field-effect transistors using weak nonlocality approximation

Abstract: We develop an analytical device model for graphene bilayer field-effect transistors (GBL-FETs) with the back and top gates. The model is based on the Boltzmann equation for the electron transport and the Poisson equation in the weak nonlocality approximation for the potential in the GBL-FET channel. The potential distributions in the GBL-FET channel are found analytically. The source-drain current in GBL-FETs and their transconductance are expressed in terms of the geometrical parameters and applied voltages b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Graphene transistors, like CNTFET, can have a variety of back gates and combined gates (upper and lower) [131,132]. Single-layer graphene field effect transistors with an energy band gap of zero and two-layer ones with finite energy band gap have been theoretically studied and their characteristics have been reported by many studies [133][134][135][136][137][138][139][140][141]. With a honeycomb structure of an atomic layer width, graphene was mechanically separated from graphite for the first time in late 2004 [142].…”
Section: Transistors Based On Graphene and Carbon Nanotubesmentioning
confidence: 99%
“…Graphene transistors, like CNTFET, can have a variety of back gates and combined gates (upper and lower) [131,132]. Single-layer graphene field effect transistors with an energy band gap of zero and two-layer ones with finite energy band gap have been theoretically studied and their characteristics have been reported by many studies [133][134][135][136][137][138][139][140][141]. With a honeycomb structure of an atomic layer width, graphene was mechanically separated from graphite for the first time in late 2004 [142].…”
Section: Transistors Based On Graphene and Carbon Nanotubesmentioning
confidence: 99%
“…The design of highfrequency (HF) circuits using these emergent devices requires an appropriate description of its behavior. Many GFET models have been proposed comprising large-signal and small-signal varieties [3][4][5][6][7][8][9][10][11][12][13][14][15][16] but all of them based on a quasi-static (QS) approximation, where the fluctuation of the varying terminal voltages is assumed to be slow, so the stored charge in the device could follow the voltage variations. Such an approximation is found to be valid when the transition time for the voltage to change is less than the transit time of the carriers from source to drain.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the first observation of current saturation in zero-bandgap, top-gated graphene field-effect transistors was reported by Shephard et al [3], and Rogers [4] discussed the synthesis of ultrathin films of reduced graphene oxide with large area and their possible utilization in flexible electronics and other applications. Ryzhii et al investigated the tunneling currentvoltage characteristics of graphene and graphene nanoribbon field-effect transistors [5,6], the device model for graphene bilayer field-effect transistors [7], high-frequency properties of graphene nanoribbon field-effect transistors [8] and an analytical device model for graphene bilayer field-effect transistors, using a weak nonlocality approximation [9]. In reference [10] Duan et al demonstrated the fabrication of high-speed graphene transistors with a self-aligned nanowire Original content from this work may be used under the terms of the Creative Commons Attribution 3.0 licence.…”
Section: Introductionmentioning
confidence: 99%